Embedded Liberalism and its Critics - Steffek, J. author. aut Link
XII, 215 p. 1 illus. in color.
Keywords: Focusing on the development of justificatory discourse on global governance, Steffek examines how differing conceptions of distributive and social justice have played a role in negotiations in the domains of security, economics, and protecting the environment.